Perbandingan Metode SAW Dan TOPSIS Dalam Penentuan Lulusan Mahasiswa Terbaik (Studi Kasus : Prodi TI Universitas Pamulang) - Nurul Huda Hakim; Achmad Udin Zailani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Pamulang University (UNPAM) South Tangerang is one of the private higher education institutions capable of producing quality intellectuals. To get the best graduates, both study programs or graduation equipment. The basis for awarding the best graduate is the GPA (GPA). However, in the process of selecting the best graduates, they are often faced with a situation where there are those who have the same Grade Point Average (GPA), in this case the institution is difficult to determine who is the best because it only uses one variable. Seeing the existing problems, the purpose of this study is to compare the Technique for Order Performance of Similarity to Ideal Solution (TOPSIS) method with the Simple Additive Weighting (SAW) method to identify the problems that occur. In this study, researchers used 2 methods at once to look for comparisons. Which method is better in overcoming the problem of determining the best student graduates. In implementing this method, the application uses the PHP programming language, and the data storage uses MySQL. based on 5 assessment criteria (GPA, study period, total D score, TOEFL score, passed LSP competence) in the selection process for the best graduates, the results of the comparison of the Technique For Order Preferences By Similarity To Ideal Solution (TOPSIS) and Simple Additive Weighting (SAW) methods. Simple Additive Weighting (SAW). The results show that the TOPSIS method has a slightly faster average time of calculation compared to the Simple Additive Weighting (SAW) method. So, the Technique For Order Preferences By Similarity To Ideal Solution (TOPSIS) method is a better method based on the processing time between these two methods.